The Shift In The Ecumenical Church Paradigm A Historical Study Of The Shift In The Ecumenical Paradigm In GMIM From 1934 To 2016 - Riedel Christian Gosal (Green Publisher Indonesia, 2024)
Global changes occur in all aspects of human life. The church as a community in the midst of society is also not spared from the impact of change due to changing times. The Evangelical Church in Minahasa is a church that grows and develops in the midst of Minahasa society which is also experiencing changes. Change gave birth to a new paradigm in the church. The problem is whether the change is a synthesis of the old and new paradigms or really gives birth to a new paradigm? Perhaps even a return to the old ecclesiological order adapted to the current context? GMIM has historically tried to answer its calling in the midst of a changing world. GMIM is the largest church in North Sulawesi that has influenced the development of the region. Ecumenism in the local church is strongly influenced by the ecclesiology set by the church. In this paper, the author uses a qualitative method and uses a historical research approach to dissect changes in the ecumenical paradigm from 1934-2016. The author compares ecumenical theories from several Indonesian and foreign figures and theories about paradigm shifts. The results show that there was a shift in GMIM ecumenical ecclesiology through the discussion of sessions, seminars, discussions among theological experts.